Outcomes associated with dual antiplatelet therapy after myocardial infarction in patients with aortic stenosis. (15th April 2019) - Martinsson, Andreas; Li, Xinjun; Torp-Pedersen, Christian; Zöller, Bengt; Andell, Pontus; Andreasen, Charlotte; Gislason, Gunnar; Køber, Lars; Sundquist, Kristina; Smith, J. Gustav; Andersson, Charlotte
Abstract: Background: Acquired loss of the largest von Willebrand factor multimers is a common hemostatic disturbance in patients with aortic valve stenosis (AS), resulting in impaired platelet adhesion and increased bleeding risk. AS is also associated with atherosclerosis and myocardial infarction (MI). Our aim was to study the clinical outcomes associated with AS in MI patients treated with dual antiplatelet therapy (DAPT) in a nationwide hospital-based register study. Methods: Based on nationwide hospital discharge registers from Sweden (2005–2010) and Denmark (2005–2015), we calculated 1-year incidence rates and hazard ratios of bleeding, recurrent MI, and all-cause mortality in MI patients with and without AS treated with DAPT. Results from both countries were also combined in a meta-analysis. Results: We included 50, 460 MI patients from Sweden and 50, 307 MI patients from Denmark, of which 3% had AS. The bleeding rates (per 100 person-years) in Sweden and Denmark were 3.2 and 3.3 among patients without AS vs. 9.2 and 8.3 among patients with AS. All-cause mortality rates were 7.1 vs. 28.7 in Sweden and 5.8 vs. 30.7 in Denmark among patients without and with AS, respectively. Patients with AS had an increased risk of bleeding, recurrent MI and all-cause mortality. Combined results from both countries were similar for bleeding (hazard ratio 1.59 [0.98–2.59]), recurrent MI (1.78 [1.25–2.54]), and all-cause mortality (1.76 [1.26–2.47]). Conclusion: AS was associated with an increased risk of bleeding, recurrent MI and mortality after MI when treated with DAPT. Individualized selection of antiplatelet therapy may be warranted in this high-risk population. Highlights: Bleeding was more common in AS patients treated with DAPT after MI. Recurrent MI and all-cause mortality were more frequent in AS patients. Patients with AS represent a group with high risk after incident MI.